Oxyphenbutazone improves memory and learning impairments in LPS-induced neurotoxicity via modulating TGF-β/NF-κB/IκB-α pathways: In silico and in vivo study - Khalid Saad Alharbi; Muhammad Afzal; Sattam Khulaif Alenezi; Reem ALQahtani; Tariq G. Alsahli; Faisal Imam; Imran Kazmi (PLoS ONE, 2026)
Objective Neuroinflammation and oxidative stress play key roles in cognitive decline and memory impairments. This study employed a lipopolysaccharide (LPS)-induced neurotoxicity model and in silico methods, including in silico docking and dynamic simulations, to assess the therapeutic potential of Oxyphenbutazone (OPB). Materials and methods Wistar rats were categorized as control, LPS-only section, LPS + OPB receiving low (35 mg/kg) and high (70 mg/kg) doses of OPB, and only OPB (70 mg/kg) doses. Behavioral assessments (Y-maze and Morris water tests) were used to assess cognitive ability. The levels of neuroinflammatory markers [Interleukin-6 (IL-6), IL-1β, and tumor necrosis factor-alpha (TNF-α)] and oxidative stress modulators [Superoxide dismutase (SOD), glutathione (GSH), catalase (CAT), and malondialdehyde (MDA)] were estimated. Additionally, transforming growth factor-beta (TGF-β), nuclear factor-kappa B (NF-κB), and inhibitor of kappa B-alpha (IκB-α) levels were evaluated. In silico analyses, such as molecular docking and dynamic simulations, were used to evaluate the stability of OPB and target molecules. Results Cognitive performance improved after OPB treatment, and the levels of proinflammatory cytokines, antioxidants, TGF-β, NF-κB, and IκB-α were restored. Additionally, in silico analyses illustrated favorable and stable interactions between OPB and the target molecules NF-κB and IκB-α. Conclusion These findings suggest the therapeutic potential of OPB in mitigating neurotoxicity and the associated cognitive disabilities.